Podaxis littoreus (Agaricaceae, Agaricales), a novel coastal species from Hainan Island, tropical China - Han, Yun-Xiao; Zhao, Lei; Yuan, Lang-Xing; Zeng, Yu-Qin; Wang, Yi; Xue, Mei-Li; Mu, Xiao-Dong; Zeng, Nian-Kai (Phytotaxa, 2026)
The fungal genus Podaxis has long attracted research interest, with approximately 58 published taxonomic records. Given its ongoing taxonomic expansion, further field surveys are likely to reveal additional novel species within the genus. During recent fieldwork in Hainan Island, a tropical region of China, specimens resembling Podaxis were collected. Through integrated morphological and molecular phylogenetic analyses, a new species, P. littoreus, was described, which is characterized by a whitish brown to dark brown basidioma, relatively large and thick-walled basidiospores (2–3 μm thick), and occurrence in sandy, saline coastal soils. This study provides a detailed description of P. littoreus, clarifies its phylogenetic position, and enhances the taxonomic and biogeographic understanding of the genus Podaxis.